Effect of the new immunoregulator AS-101 on in vitro functions of mononuclear cells from patients with systemic lupus erythematosus. - Alcocer-Varela, J (1989)
We studied the in vitro production of interleukin-2 (IL-2), the expression of IL-2 receptors, the absorption of IL-2, and spontaneously expanded suppressor cell function by mononuclear cells from 15 patients with systemic lupus erythematosus (SLE) and 15 healthy control subjects. These functions were studied in the presence or absence of AS-101, a recently described organotellurium compound with immunoregulatory properties. AS-101 was found to be non-toxic to cells from both patient and control groups; it increased the production of IL-2, elevated the percentage of Tac-positive cells even among cells that had been pre-treated with pronase, and ameliorated the absorption of IL-2. It also enhanced the suppressor cell function in cells from SLE patients. Since these functions are known to be defective in vitro in cells of SLE patients, and since preliminary testing of AS-101 in humans indicates that it is a safe drug, this immunoregulatory compound holds promise for a novel and effective treatment of SLE.